Europe for the Europeans the foreign and security policy of the populist radical right - Liang, Christina Schori (Ashgate Pub., 2007)
The number of political organizations on the far right, neo-populist right and neo-conservative right have been growing in number. This book measures the effects of neo-populist groups on the political establishment and illustrates how much political appeal neo-populist views have on making political policy.